PENGARUH KERJA SHIFT TERHADAP TEKANAN DARAH, DENYUT NADI, DAN KESEHATAN MENTAL PERAWAT RUMAH SAKIT AMC CILEUNYI - Eko Prasetyo (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2022)
Shift workers have a higher risk of health problems than daily workers. Shift workers experience circadian rhythm disturbances. Circadian rhythm disorders can increase the risk of cardiovascular disease due to changes in hormone secretion, neurotransmitters, metabolism, heart rate, and autonomic heart control. Neurotransmitters are influenced by circadian rhythm are one of norepineprin, epinephrine and serotonin which can affect the mental health stage. This research is an observational analytic study with primary data. From the data collection, 33 people met the inclusion and exclusion criteria. The results of taking blood pressure were normal (84,9%) and abnormal (15,2%). The heart rate is normal (90,9%) and abnormal (9,1%). Mild anxiety disorders (12,1%), normal (87,9%). Low depression (9,1%), limit depression (9,1%), normal (81,8%). Work shift has a significance value of t-test 0.503> α and a coefficient of determination of 1,5% for blood pressure. Work shift has a significance value of a t-test of 0.549> α and a coefficient of determination of 1,2% of the heart rate. Work shift has a significance value of t-test 0.502 <α and a coefficient of determination of 1,5% for anxiety disorders. Work shift has a significance value of the t-test of 0.103> α and a coefficient of determination of 8,3% for depression. Conclusions There is no effect of shift work on blood pressure, heart rate, anxiety disorders, and depression.